2011
DOI: 10.1155/2011/986409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Oxadiazoline and a Lignan on Mycolic Acid Biosynthesis and Ultrastructural Changes ofMycobacterium tuberculosis

Abstract: Tuberculosis (TB) is an important disease that causes thousands of deaths around the world. Resistance against antitubercular available drugs has been reported; so, research on new effective antimycobacterial molecules is needed. Antimycobacterial activity of three lignans and two synthetic hydrazones was assessed against Mycobacterium tuberculosis H37Rv by antimycobacterial microdilution assay (TEMA). An oxadiazoline (AC451) and a lignan (ethoxycubebin) were the most active compounds (MIC 6.09 and 62.4 μM, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…prop-2-en-1-one (30 µg/mL) [45] cordiachrome C (1.5 µg/mL) [52] aromatic alkene, and pyrrolidine amide (25 µg/mL) [69] 5,4′-dihydroxy-3,7,8,3′-tetramethoxy flavones (> 50 µg/mL) (25 µg/mL) [28] palmarumycin JC2 (6.25 µg/mL) [39] Isobavachalcone (18 µg/mL) [45] globiferin (6.2 µg/mL) [52] tetrahydroxy squalene (10 µg/mL) [70] 5,4′-dihydroxy-3,7,8-trimethoxyflavone (> 50 µg/mL) (25-50 µg/mL) [28] α-tocopheryl quinone (25 µg/mL) [40] scopoletin (42 µg/mL) [45] diol derivative of labdane (250 µg/mL) [53] trans,trans-1,7,diphenylhepta-4,6-dien-3-one (> 128 µg/mL) [71] nevadensin and isothymusin (200 µg/mL) [29] 2′,5′′-dimethoxysesamin (63 µg/mL) [47] dioxime derivative of labdane and labdane (500 µg/mL) [53] xanthones (10 µg/mL) [72] pisonivanone (12.5 µg/mL) [32] ethoxycubebin (62.4 µM) [49] caniojane (25 µg/mL) [54] continued phytol derivatives (15.6-50 µg/mL) [64] phytol (100 µg/mL) [64] zylamine (2) inhibited both the sensitive and MDR strains of M. tuberculosis at minimum inhibitory concentrations (MIC) of 50 and 200 µg/mL, respectively [8]. Justicia adhatoda L., Acanthaceae, is known as vasaka in the Indian system of medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…prop-2-en-1-one (30 µg/mL) [45] cordiachrome C (1.5 µg/mL) [52] aromatic alkene, and pyrrolidine amide (25 µg/mL) [69] 5,4′-dihydroxy-3,7,8,3′-tetramethoxy flavones (> 50 µg/mL) (25 µg/mL) [28] palmarumycin JC2 (6.25 µg/mL) [39] Isobavachalcone (18 µg/mL) [45] globiferin (6.2 µg/mL) [52] tetrahydroxy squalene (10 µg/mL) [70] 5,4′-dihydroxy-3,7,8-trimethoxyflavone (> 50 µg/mL) (25-50 µg/mL) [28] α-tocopheryl quinone (25 µg/mL) [40] scopoletin (42 µg/mL) [45] diol derivative of labdane (250 µg/mL) [53] trans,trans-1,7,diphenylhepta-4,6-dien-3-one (> 128 µg/mL) [71] nevadensin and isothymusin (200 µg/mL) [29] 2′,5′′-dimethoxysesamin (63 µg/mL) [47] dioxime derivative of labdane and labdane (500 µg/mL) [53] xanthones (10 µg/mL) [72] pisonivanone (12.5 µg/mL) [32] ethoxycubebin (62.4 µM) [49] caniojane (25 µg/mL) [54] continued phytol derivatives (15.6-50 µg/mL) [64] phytol (100 µg/mL) [64] zylamine (2) inhibited both the sensitive and MDR strains of M. tuberculosis at minimum inhibitory concentrations (MIC) of 50 and 200 µg/mL, respectively [8]. Justicia adhatoda L., Acanthaceae, is known as vasaka in the Indian system of medicine.…”
mentioning
confidence: 99%
“…Among them, cinerin C (80) showed a half inhibition of mycobacterium at a concentration of 50 µg/mL. The lignan which disrupts mycolic acid biosynthesis, ethoxycubebin (82), was isolated from Virola flexuosa L., Myrstiaceae, with moderate activity (MIC 62.4 µM) and no cytotoxicity [49].…”
mentioning
confidence: 99%
“…MIC values towards M. tuberculosis H37Rv for compound 68 was 6.09 µM and for compound 69 it was 81.1 µM, whereas for INH it was 0.438 µM and for rifampicin (RFP): 0.608 µM (Fig. 22) (Baquero et al 2011).…”
Section: Antitubercular Activitymentioning
confidence: 96%
“…Isoniazid (INH) was used as reference substance (Joshi et al 2008). Baquero et al (2011) in research article presented two oxadiazole derivatives, which showed antitubercular activity (68, 69) (Fig. 22).…”
Section: Antitubercular Activitymentioning
confidence: 99%
“…Plants: Drugs based on plants extracts have been used worldwide for the treatment of several diseases from ancient times.A great interest in phytomedicine and natural product structures are screened in order to measure their pharmacologic activity. In Colombia, there has been a resurgent interest in the discovery of novel natural anti-TB drugs [50][51][52][53][54].…”
Section: Survey Of Natural Productsmentioning
confidence: 99%